Increasing the Efficacy of GA3 Sprays in Cluster Elongation and Berry Thinning in Tas-A-Ganesh Grape (Vitis vinifera L.) in Tropical Viticulture - S D Shikhamany; V Swapnil Borade; K Sanjay Jeughale; Suryakant Y Patil (Journal of Horticultural Sciences, 2018)
In view of the stage specificity for the efficacy of blanket sprays of GA3 for berry thinning, a field trial was laid out to achieve uniform flowering in Tas-A-Ganesh grapevines subjected to chemical defoliation prior to and hydrogen cyanamide application at fruit pruning in the double pruning and single cropping system during 2013-14 and 2014-15 fruiting seasons in growers’ vineyards around Nashik, Maharashtra by removing the un-uniformly thick canes. GA3 at different doses was sprayed two or three times to address the variation in uniform flowering, if any in cluster elongation and reducing the berry number/cluster. Cane regulation and GA3 sprays were used to achieve uniformity in bud break and flowering. Cluster compactness was derived by multiplying the number of berries/ cm length of rachis with berry diameter. Regression analysis of the variation has revealed that the cane diameter, through uniformity in bud break, influenced the uniformity in flowering which in turn influenced the cluster compactness through increased efficacy of blanket GA3 sprays in reducing the berry number/ cluster. Based on the optimum values of the contributory factors to cluster compactness, cane removal coupled with two blanket sprays of GA3 @ 30 g a.i./ha or retention of all canes coupled with three blanket sprays of GA3 @ 20 g a.i./ha was found to be ideal to obtain loose to well filled clusters. Taking together into account the effect of treatments on cluster compactness, yield and quality, retention of all canes coupled with three sprays of GA3 @ 20 g a.i./ha was considered appropriate for table grape production in Tas-A-Ganesh cv. of grapes.